IMPACT OF MODIFIED FEED MECHANISM ON SEAM QUALITY OF GARMENTS - RAHMAN Mohammad Faizur; ALAM Mohammad Ashraful; HOSSAIN Kazi Rezwan; BARAL Lal Mohan; SARKAR Mahadi Hasan; SARKAR Prosenjit; RASHID Mohammad Rafiqur (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2023)
A few distinct feed mechanisms can be found in sewing machines. The mechanism that feeds the material into the machine differs in each machine. In lock stitch sewing machines, the mechanism known as the drop feed is the one that is utilized the majority of the time. Its construction includes one presser foot, one throat plate, and one feed dog. Different types of feed dogs can be used in the drop feed mechanism to achieve the desired level of customization. In this study, modification-1, modification-2, and modification-3 were created in an industrial lock stitch machine using feed dogs with 18, 21, and 30 teeth, respectively. These numbers correspond to the number of teeth on the feed dogs. The quality of the seams, such as the seams on garments, was analyzed after each modification of the feed mechanism performed on seams made of the same fabric (Denim fabric). We took measurements of the seam's strength and efficiency as well as its puckering and slippage. It was discovered that the seam quality of garments constructed using modification-1 (one) is superior to that of garments constructed using the other two modifications using the same fabric. Therefore, to finish a specific garment accurately, it is necessary to select the appropriate sewing machine and ensure that it has the ideal feed mechanism.